Radioablation of Upper Abdominal Malignancies by CT-Guided, Interstitial HDR Brachytherapy: A Multivariate Analysis of Catheter Placement Assisted by Ultrasound Imaging - Damm, Robert; Damm, Romy; Heinze, Constanze; Surov, Alexey; Omari, Jazan; Pech, Maciej; Powerski, Maciej (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose To evaluate the use of ultrasound (US) during catheter placement in interstitial brachytherapy (iBT) of abdominal malignancies as an alternative to computed tomography (CT) fluoroscopy.Materials and Methods Catheter placement for CT-guided iBT was, if US visibility was sufficient, assisted by sonography in 52 consecutive patients with 82 lesions (liver N = 62; kidney N = 16; peritoneum N = 4) of various malignancies. We collected data on lesion visibility, location, depth, size, and dosimetry. Comparison of CT fluoroscopy versus US-assisted catheter placement was performed by Fisher’s exact test for frequencies and U-test for lesion visibility and dosimetric data. Factors predicting the utility of sonography were determined in a lesion-based multivariate regression analysis. A p-value < 0.05 was regarded as statistically significant.Results 150 catheters (1 to 6 per lesion; mean diameter 3.6 ± 2.4 cm) were implanted. CT fluoroscopy was used for 44 catheters, and US was used for 106 catheters. Lesion visibility assessed by 5-point Likert scale was significantly better in US (median 2 vs. 3; p = 0.011) and effective dose was significantly reduced if US guidance was applicable (median 1.75 vs. 8.19 mSv; p = 0.014). In a multivariate regression analysis, we identified increased lesion size and caudal location within the target organ to independently predict the utility of ultrasound in catheter placement for iBT.Conclusion Sonography is a helpful technique to assist CT-guided interstitial brachytherapy of upper abdominal malignancies. Especially for larger lesions localized in the lower liver segments or lower half of the kidney, superior visibility can be expected. As the effective dose of the patient is also reduced, radiation exposure of the medical staff may be indirectly lowered.Key Points: Citation Format
Keywords: brachytherapy; local ablative treatment; sonography